STABILITY-INDICATING METHOD FOR DETERMINATION OF TIZANIDINE HYDROCHLORIDE IN PHARMACEUTICAL LC-CAD METHOD USING CHEMOMETRIC APPROACH - Mariana Brandalise; Pamela Cristina Lukasewicz Ferreira; Andrea Garcia Pereira; Leonardo Meneghini; Pedro Eduardo Fröehlich; Ana Maria Bergold (Drug Analytical Research, 2017)
A new LC method for tizanidine hydrochloride in tablet dosage form using a charged aerosol detector (CAD) is described. The influence of various parameters on chromatographic system was investigated by factorial designs and Derringer's desirability. Chromatographic conditions were: mobile phase constituted of acetonitrile and ammonium acetate buffer 17 mM (60:40; v/v), column oven at 39 °C and flow rate 0.8 mL.min-1 performed in on Acclaim Trinity P1 column UV at 230 nm. Thus, it was possible to validate a simple method to assay the tizanidine and its counter-ion in three formulations (drug reference, generic and manipulated). Method showed specificity when challenged by forced degradation and excipients. Finally, the method was compared with USP monograph method demonstrating equivalence in assay evaluation.